2020
DOI: 10.1177/0959683620972764
|View full text |Cite
|
Sign up to set email alerts
|

A 2000-year documentary record of levee breaches on the lower Yellow River and their relationship with climate changes and human activities

Abstract: The Yellow River floodplain represents a fertile landmass that contributes significantly to human welfare and thus has been colloquially known as the birthplace of Chinese civilization. The sediment-laden nature of the Yellow River gave rise to a super-elevated channel belt, which is prone to failure particularly in the summer months when excessive precipitation occurs, resulting in cataclysmic floods traditionally regarded as “China’s Sorrow.” Therefore, a deeper understanding of levee breach frequency in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 69 publications
(118 reference statements)
1
9
0
Order By: Relevance
“…After the end of the LIA, a warming trend occurred that lasted into the 20C WP, and within the 20C WP, the globally averaged surface temperatures over land and ocean showed a linear warming trend of 0.85 °C from 1880 to 2012 CE ( Intergovernmental Panel on Climate Change (IPCC), 2014 ; Zhou et al, 2021 ). According to previous studies, the increased frequency and severity of meteorological disasters can be found during the 20C WP ( Shi, Cui & Tian, 2020 ; Li et al, 2021b ; Li, Li & Zhang, 2020 ; Xing et al, 2020 ; Zhou et al, 2021 ), and our record also indicated the major meteorological disasters occurred frequently since 1911 CE ( Figs. 3 and 4B ).…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…After the end of the LIA, a warming trend occurred that lasted into the 20C WP, and within the 20C WP, the globally averaged surface temperatures over land and ocean showed a linear warming trend of 0.85 °C from 1880 to 2012 CE ( Intergovernmental Panel on Climate Change (IPCC), 2014 ; Zhou et al, 2021 ). According to previous studies, the increased frequency and severity of meteorological disasters can be found during the 20C WP ( Shi, Cui & Tian, 2020 ; Li et al, 2021b ; Li, Li & Zhang, 2020 ; Xing et al, 2020 ; Zhou et al, 2021 ), and our record also indicated the major meteorological disasters occurred frequently since 1911 CE ( Figs. 3 and 4B ).…”
Section: Discussionsupporting
confidence: 84%
“…4C ). Previous studies have shown that the temperature changes in the Henan Province were highly consistent with those in most regions of China, whether it is the warming trend in the 20th century or the century-scale warming and cooling phases in the past 2,000 years ( Ge et al, 2016 ; Zheng et al, 2014a ; Li et al, 2021b ). Among them: during the Han Dynasty (100 BCE–200 CE), Sun and Tang Dynasties (550–850 CE), Song and Yuan Dynasties (950–1300 CE) and the 20th century, the climate was relatively warm and other periods were relatively cold ( Figs.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations